Measuring The Gig Economy in Indonesia: Typology, Characteristics, and Distribution - Permana, Muhammad Yorga; Izzati, Nabiyla Risfa; Askar, Media Wahyudi (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2022)
Abstract. Work in the gig economy is defined as short-term and task-based jobs mediated by digital platforms. In Indonesia, the emergence of an online motorcycle taxi driver platform in 2015 marked the discourse about the gig economy as the future alternative of jobs on the one hand, and as a new form of exploitation of labor on the other hand. This study is the first to define the typology of the gig economy and identify the platforms of the gig economy service providers in Indonesia. Furthermore, this study estimates the number of gig economy workers by using micro data from the National Labor Force Survey (Sakernas) released by the Central Statistics Agency. It was found that 0.3 to 1.7% of Indonesian workers participated in the gig economy as their primary job. This study also compares the characteristics of gig workers in the transportation sector and in the other service sectors with the overall demographics of the workforce. It was found that gig workers shared more characteristics with the formal workers than with the informal workers. Finally, this study maps the distribution of gig workers throughout Indonesia at the city/district level. It can be concluded that the gig economy is an urban phenomenon. Most gig workers in the transportation sector are concentrated in the provincial capital and in Metropolitan Jakarta. Meanwhile, gig workers in other service sectors are distributed more in tier 2 cities in Java.Keywords: Gig economy, gig worker, digital worker, labor economics, jobs Abstrak. Pekerjaan di dalam ekonomi gig didefinisikan sebagai pekerjaan berbasis tugas jangka pendek yang dimediasi oleh platform digital. Di Indonesia, kehadiran platform pengemudi ojek online di tahun 2015 menandai ramainya wacana mengenai ekonomi gig sebagai kesempatan pekerjaan di masa depan di satu sisi dan juga sebagai bentuk baru eksploitasi pekerja di sisi lain. Studi ini merupakan yang pertama mendefinisikan tipologi ekonomi gig dan memetakan platform penyedia layanan ekonomi gig di Indonesia. Lebih lanjut studi ini juga mengestimasi ukuran pekerja ekonomi gig menggunakan data mikro survei angkatan kerja nasional (Sakernas) yang dirilis oleh Badan Pusat Statistik. Didapatkan bahwa terdapat 0,3 hingga 1,7% dari angkatan kerja Indonesia yang menjadikan ekonomi gig sebagai pekerjaan utamanya. Kemudian, studi ini membandingkan karakteristik pekerja gig di sektor transportasi dan di sektor jasa lainnya dengan demografi pekerja keseluruhan. Didapatkan bahwa pekerja gig memiliki karakteristik lebih mirip dengan pekerja formal daripada pekerja informal. Terakhir, studi ini memetakan sebaran pekerja gig di seluruh Indonesia hingga ke tingkat Kota/Kabupaten. Dapat disimpulkan bahwa ekonomi gig merupakan fenomena urban. Pekerja gig di sektor transportasi banyak terkonsentrasi di Ibukota provinsi dan di Metropolitan Jakarta. Sementara pekerja gig di sektor jasa lainnya lebih terdistribusi ke kota-kota tier 2 di Pulau Jawa.Kata kunci: Ekonomi gig, pekerja gig, pekerja digital, ekonomi tenaga kerja, pekerjaan